2018
DOI: 10.2147/ijn.s163929
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured lipid carriers co-delivering lapachone and doxorubicin for overcoming multidrug resistance in breast cancer therapy

Abstract: BackgroundMultidrug resistance is responsible for the poor outcome in breast cancer therapy. Lapa is a novel therapeutic agent that generates ROS through the catalysis of the NAD(P) H:quinone oxidoreductase-1 (NQO1) enzyme which significantly facilitate the intracellular accumulation of the co-delivered DOX to overcome MDR in cancer cells.PurposeHerein, in our study, nanostructured lipid carrier (NLC) co-delivering β-lapachone (Lapa) and doxorubicin (DOX) was developed (LDNLC) with the aim to overcome the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“… 13 However, the codelivery of both drugs in one DDS, which integrates decent drug-loading capacity and promising tumor targetability, is a critical issue that requires careful selection of suitable carrier. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“… 13 However, the codelivery of both drugs in one DDS, which integrates decent drug-loading capacity and promising tumor targetability, is a critical issue that requires careful selection of suitable carrier. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Etoposide encapsulated in transferrin-conjugated nanostructured lipid carriers efficiently targeted acute myelogenous leukemia cells, 174 and induced cytotoxicity in human gastric cancer cell lines and on tumor animal models 175 . NLCs delivering lapachone and doxorubicin were able to overcome multidrug resistance in breast cancer experimental models 176 . Co-delivery of paclitaxel and indocyanine green was also successful in combining chemo- and photodynamic therapy in vitro and in vivo.…”
Section: Nanocarriers For Therapymentioning
confidence: 99%
“…In vitro studies on MCF-7 ADR cells showed increased uptake of doxorubicin when given in combination. In in vivo studies on MCF-7 ADR, tumor-bearing mice revealed enhanced efficacy when administered in combination, as compared to doxorubicin monotherapy [ 156 ]. Phytochemical resveratrol also showed improved efficiency when loaded into NLCs tethered with folic acid [ 157 ].…”
Section: Nanomedicine Used In the Management Of Breast Cancermentioning
confidence: 99%